Active prescription of low-dose aspirin during or prior to hospitalization and mortality in COVID-19: A systematic review and meta-analysis of adjusted effect estimates. (July 2021) - Martha, Januar Wibawa; Pranata, Raymond; Lim, Michael Anthonius; Wibowo, Arief; Akbar, Mohammad Rizki
Highlights: Low-dose aspirin was independently associated with reduced mortality in COVID-19 patients. The certainty of evidence was low and requires further investigation. In-hospital administration of low-dose aspirin was associated with reduction in mortality. Abstract: Background: This study aimed to investigate whether the active prescription of low-dose aspirin during or prior to hospitalization affects mortality in patients with coronavirus disease 2019 (COVID-19). Aspirin is often prescribed for secondary prevention in patients with cardiovascular disease and other comorbidities that might increase mortality, and may therefore falsely demonstrate increased mortality. To reduce bias, only studies that performed an adjusted analysis were included in this review. Methods: A systematic literature search of PubMed, Scopus, Embase and Clinicaltrials.gov was performed, from inception until 16 April 2021. The exposure was active prescription of low-dose aspirin during or prior to hospitalization. The primary outcome was mortality. The pooled adjusted effect estimate was reported as relative risk (RR). Results: Six eligible studies were included in this meta-analysis, comprising 13, 993 patients. The studies had low-to-moderate risk of bias based on the Newcastle–Ottawa Scale. The meta-analysis indicated that the use of low-dose aspirin was independently associated with reduced mortality {RR 0.46 [95% confidence interval (CI) 0.35–0.61], P < 0.001; I 2 = 36.2%}. Subgroup analysis on in-hospital low-dose aspirin administration also showed a significant reduction in mortality [RR 0.39 (95% CI 0.16–0.96), P < 0.001; I 2 = 47.0%]. Conclusion: Use of low-dose aspirin is independently associated with reduced mortality in patients with COVID-19, with low certainty of evidence.